Feasibility of endoscopic submucosal dissection for cecal lesions. (4th March 2018) - Suzuki, Takuto; Hara, Taro; Kitagawa, Yoshiyasu; Takashiro, Hideyuki; Nankinzan, Rino; Yamaguchi, Taketo
Abstract: Background: The treatment results of endoscopic submucosal dissection (ESD) for colorectal lesions have improved markedly, but some lesions remain difficult to treat. Hence the cecum is considered a technically challenging site for ESD. We examined the feasibility of ESD for cecal lesions. Methods: Among a total of 708 colorectal ESD performed in our hospital between March 2006 and December 2016, 549 procedures performed after April 2012 were studied, at a time when the techniques of ESD had stabilized and the procedure was covered by health insurance in Japan. Among 549 cases, 61 were cecal lesions and 488 were noncecal lesions. The treatment outcomes were analyzed. Results: For cecal lesions, the en bloc resection rate was 95.1%, R0 resection rate was 91.8%, perforation rate was 0%, delayed bleeding rate was 6.6%, median diameter of resected specimen was 32 mm (16–65 mm), median time of the procedure was 44 minutes (8–140 min). The corresponding results for noncecal lesions were 97.3%, 95.5%, 0.4%, 2.7%, 30 mm (10–109 mm), and 37 min (7–225 min). No significant differences were observed and the good treatment results were seen. When the outcomes were analyzed for cecal sites considered to be particularly challenging; proximity to appendiceal orifice, the ileocecal valve, and the bottom of cecum, the treatment results were not inferior to other sites. Conclusions: ESD is safe and effective even for cecal lesions considered challenging to treat. ESD is feasible for cecal lesions.